Moderate External Rotation of Tibial Component Generates More Natural Kinematics Than Internal Rotation After Total Knee Arthroplasty - Fang, Chaohua; Luan, Yichao; Wang, Zhiwei; Shao, Long; Qu, Tiebing; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2022)
This study aimed to investigate the influence of tibial malrotation on knee kinematics after total knee arthroplasty(TKA). A symmetric fixed-bearing posterior stabilized prosthesis was implanted in the validated knee model with different rotational alignments of the tibial component(neutral, 3° external rotation, 5° external rotation 3° internal rotation, 5° internal rotation). Computational kinematic simulations were used to evaluate the postoperative kinematics of the knee joint including anteroposterior translation femoral condyles and axial rotation of tibial component during 0° to 135° knee flexion. The results revealed that the neutral position of the tibial component was not the closest kinematics to the intact knee, the model with 5° external rotation of the tibial component showed the closest lateral condyle translation and tibial axial rotation, the moderate external rotation could improve the kinematics after TKA.